Do Material Reciclável Sobreviver, Resistir e dele uma Identidade Construir - Gonçalves, Marilene Parente (2007)
The present work results from a search to understand the meaning of organization and recycling material collector fight, who show themselves through MNCR (National Movement of Recycling Material Collectors). This work is also a product of the search for comprehension to their identity building, using as research field the speeches from the referred movement representatives in Rio de Janeiro. In order to it, poverty, identity and social movements were selected to analysis. We know that, the present society, at the same time it amasses gains, it also supports the lost to a meaningful part of relegated individuals to marginality and poverty condition. If they begin doing degrading activities on society eyes, they suffer a social branding process, and they are considered second rate. The meeting of poverty and trash, mainly recycling material, suffers this branding. However, this meeting shows new ways of being in society, which are identified by the trash collectors. Saved by them, the work with recycling material brings the possibility for an identity formation, the collector identity which guards their work value and dignity while social being. The used way to this defense is through organization in social movements, the MNCR .It is a self collector movement, which searches for social and legal admission of their occupation, fighting for a National Politics and Solid Residue approvement. They turn to build, at the same time, the identity class, putting themselves in resistance.